Lowered blood pressure targets identify new, uncontrolled hypertensive cases: patient characteristics and implications for services in Thailand - Naphassanan Charoensab (2020)
BACKGROUND: According to the new hypertension treatment guidelines blood pressure (BP) readings need to be kept below or equal to 130/80 mmHg in patients aged less than 65 years old. This study shows the change in proportion of identified cases of uncontrolled blood pressure in light of these changes. METHODS: The data was collected from 248 hypertensive patients who had visited an outpatient clinic at the Department of Family Medicine, Faculty of Medicine, Chiang Mai University, Thailand. Patients were classified into three groups: The 3 groups were: 1) controlled BP group (BP is 130/80 mmHg or lower); 2) newly identified uncontrolled group (BP between 130/80 mmHg and 140/90 mmHg) and 3) existing uncontrolled group (BP higher than 140/90 mmHg). Health behaviors, past history related to hypertensive disease and current pharmacological treatments were compared. RESULTS: Of the total 248 patients, 56% were female and the mean age was 58.8 (sd 5.99) years old. Following application of the new guidelines, the group designated as uncontrolled increased from 21.7 to 74.2%, an additional 52.4% due to new BP targets. Higher BMI was associated with uncontrolled HT (p = 0.043). While the average number of medication taken was similar across the three groups, it was poor medication adherence (p < 0.013) which was associated with the uncontrolled disease. CONCLUSIONS: Lower BP targets will increase the number of identified hypertensive patients. While intensifying pharmacological treatment may be considered, our study suggests that two behavioral factors should not be overlooked. Weight reduction and enhancement of medication adherence remains an important mainstream treatment strategy.